2008
DOI: 10.1038/bmt.2008.296
|View full text |Cite
|
Sign up to set email alerts
|

Allo-hematopoietic cell transplantation for Ph chromosome-positive ALL: impact of imatinib on relapse and survival

Abstract: The utility of imatinib in either the pre-or post-transplant period for Ph chromosome-positive (Ph þ ) ALL is uncertain. In addition, there have been recent concerns regarding imatinib and cardiac toxicity. We investigated the outcome of 32 patients with Ph þ ALL who received an allo-hematopoietic cell transplant (HCT) at the University of Minnesota between 1999 and 2006. The median age at HCT was 21.9 years (range: 2.8-55.2). All patients were conditioned with CY and TBI. GVHD prophylaxis was CsA based. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…In contrast, most patients who started imatinib after the detection of BCR-ABL had a prompt suppression of BCR-ABL in response to the drug, and to date there is no difference in outcome between the groups. A small, nonrandomized, single-center study from the University of Minnesota 23 showed a trend toward improved outcome in patients who could be treated with imatinib in the pre-and posttransplantation period after cyclophosphamide and TBI myeloablative conditioning. Similarly, Ram et al 24 reported that imatinib given for a median duration of 11.5 months after RIC with fludarabine and 2 Gy of TBI (which was relatively well tolerated after transplantation, with only 3 of 18 patients needing to stop the drug) was associated with significantly reduced mortality on univariate analysis, although the effect on relapse was not statistically significant.…”
Section: The Role Of Tkis After Allohsctmentioning
confidence: 99%
“…In contrast, most patients who started imatinib after the detection of BCR-ABL had a prompt suppression of BCR-ABL in response to the drug, and to date there is no difference in outcome between the groups. A small, nonrandomized, single-center study from the University of Minnesota 23 showed a trend toward improved outcome in patients who could be treated with imatinib in the pre-and posttransplantation period after cyclophosphamide and TBI myeloablative conditioning. Similarly, Ram et al 24 reported that imatinib given for a median duration of 11.5 months after RIC with fludarabine and 2 Gy of TBI (which was relatively well tolerated after transplantation, with only 3 of 18 patients needing to stop the drug) was associated with significantly reduced mortality on univariate analysis, although the effect on relapse was not statistically significant.…”
Section: The Role Of Tkis After Allohsctmentioning
confidence: 99%
“…[8][9][10][11][12] Therefore, increasing attention has been paid to MRD status at allo-HCT. 13,14 Post-transplant TKI administration is another issue that has received increasing attention, 13,15,16 since relapse after allo-HCT is still one of the main problems of this disease. 1,16 Although there have been several small-scale studies on post-transplant TKI administration, [17][18][19] the utility of post-transplant TKI administration for long-term survival of Ph+ALL patients is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty studies gave a tki during consolidation or for maintenance (or both) in addition to during induction. Three studies gave imatinib before allogeneic transplantation 17,29,42 .…”
Section: 22mentioning
confidence: 99%
“…Evidence: Ten studies in 376 patients gave a tki in the post-transplantation period: eight studies administered imatinib, and two studies administered dasatinib 37,42,49,50,53,56,62,63,70,84 . Seven studies gave a tki only in the post-transplantation period.…”
Section: Question 2(b)mentioning
confidence: 99%
See 1 more Smart Citation